Pengaruh Curent Ratio, Debt Equity Ratio, Return On Asset, Sales Growth, Total Asset Turnover dan Arus Kas Operasi Terhadap Financial Destress (Studi Empiris Pada Perusahaan Real Estate dan Kontruksi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - marlina, rini (Universitas Mercu Buana, 2023)
This study aims to examine and analyze the effect of the Current Ratio, Debt Equity Ratio, Return On Assets, Sales Growth, Total Asset Turnover and Operating Cash Flow on Financial Distress. The research design used is causal research. The population of this study is all Real Estate and Construction companies listed on the Indonesia Stock Exchange for the 2019-2021 period, totaling 82 companies. The sample was taken using the non-probability method with purposive sampling technique, a sample of 56 companies was obtained so that the total research data for 3 consecutive years was 168. The research data was taken from the financial statements of each company that was sampled and obtained from the official website of the Indonesia Stock Exchange, namely https://www.idx.co.id. Data is processed using the SPSS application with multiple linear regression methods. The results of this study state that simultaneously Current Ratio, Return On Assets, and Total Asset Turnover have a significant positive effect on Financial Distress. Meanwhile, Debt Equity Ratio, Sales Growth, and Operating Cash Flow have no effect on Financial Distress.